2005
DOI: 10.1029/2005gl024349
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial occurrence of deep non‐volcanic tremor: From Washington to northern California

Abstract: [1] Regional network data reveal deep non-volcanic tremor occurs in five independent sections along the U.S. section of the Cascadia subduction zone with different recurrence intervals. Sizeable tremor episodes occur during periods with no measurable geodetic deformation as well as coincident with episodic slow slip events, and the displacement amplitudes of the tremor with and without geodetic deformation are similar. The tremor depths cover a wide range that does not coincide directly with the subducting sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(99 citation statements)
references
References 14 publications
10
89
0
Order By: Relevance
“…Since our experiments involve not only dynamical events (i.e., local unstable events which produce acoustic emission) but also very slow events compared to Rayleigh speed owing to the viscous rheology of the PMMA both in the bulk and along the contact plane, our experiment could be used as a paradigm for slow earthquakes. In this context it is of interest to note that we produce slow quakes without fluid presence contrasting to the first explanations for the slow earthquakes (SZELIGA et al, 2004;MCCAUSLAND et al, 2005;Vol. 166, 2009 Quake Catalogs from Optical Monitoring of Crack SHELLY et al, 2006;DOUBRE and PELTZER, 2007;ITO et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since our experiments involve not only dynamical events (i.e., local unstable events which produce acoustic emission) but also very slow events compared to Rayleigh speed owing to the viscous rheology of the PMMA both in the bulk and along the contact plane, our experiment could be used as a paradigm for slow earthquakes. In this context it is of interest to note that we produce slow quakes without fluid presence contrasting to the first explanations for the slow earthquakes (SZELIGA et al, 2004;MCCAUSLAND et al, 2005;Vol. 166, 2009 Quake Catalogs from Optical Monitoring of Crack SHELLY et al, 2006;DOUBRE and PELTZER, 2007;ITO et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the location uncertainty is fairly large, particularly for the focal depth, which can exceed 20 km. This method and variants on it are the most commonly used methods to locate non-volcanic tremor (e.g., McCausland et al, 2005;Wech and Creager, 2008;Payero et al, 2008).…”
Section: Waveform Envelope Location Methodsmentioning
confidence: 99%
“…While most observations of tremor, to date, have been in the Cascadia (e.g., Rogers and Dragert, 2003;Szeliga et al, 2004;McCausland et al, 2005) and the Nankai subduction zones (Obara, 2002), tremor has also been identified in the subduction zones of Alaska (Peterson and Christensen 2009), and Mexico (Payero et al, 2008), but is absent in others including the Japan Trench in northern Honshu (Obara, 2002). It has also been observed along the strike-slip plate boundary in California (Nadeau and Dolenc, 2005;Gomberg et al, 2008), the region beneath the Western Tottori earthquake in Japan (Ohmi et al, 2004), and the central Ranges of Taiwan, within Taiwanese collision zone (Peng and Chao, 2008).…”
Section: New Opportunitiesmentioning
confidence: 98%
“…Tremorcomprising LFEs in both Japan [Shelly et al, 2006] and Cascadia [Brown et al, 2009] as well as S-P wave arrival time differentials in Cascadia [La Rocca et al, 2009] also indicate that tremor occurs on the plate interface, congruent with slow slip. Constraining tremor depths is difficult and perhaps tremor does not always occur on the plate boundary and represents slip or other fluid-related deformation 10 s of km above the plate boundary [Kao et al, 2005;McCausland et al, 2005]. However, mounting evidence suggests that tremor represents slow shear, serving as a good proxy for slow slip.…”
Section: Discussionmentioning
confidence: 99%